Pembelajaran Seni Budaya (Musik) Menggunakan Media Audiovisual Pada Kelas IX Di SMP 2 Pariaman - Satria Purwadana; Irdhan Epria Darma Putra (SENDRATASIK UNP, 2020)
The purpose of this study is howthe implementation of cultural art learning media (music) using audiovisual media at class IX in SMP 2 Pariaman. Type of this research was classroom action research that was classified as qualitative research. The research method was carried out by using the class action research method proposed by Suharsimi Arikunto as follows: (1) Planning (2) Acting (3)Observing (4) Observing (4) Reflecting. Techniques of data collection used some  instrumentsin the form of students observation sheets, observations and teacher performance in learning process, meanwhile, in determining the quality of students learning outcomes used anevaluation / test sheets. he results show that the use of audiovisual learning media can improve the students learning outcomes in Cultural Arts (Music) subject. The initial average value is 70.00, in the first cycle is 71.87 and in the second cycle is 87.34.